FUNGSI PENGAWASAN DPRD DALAM MEWUJUDKAN TATA KELOLA PEMERINTAHAN YANG BAIK - Aminudin Aminudin (Katalogis, 2016)
The thesis was bassed 2 issues, i.e.: 1). How the relationship between local legislative functional and good governance is, and 2) What are the steps to enchance the local legislative functional control to assure good governance. The thesis was to identify the relationship between the legislative functional control and good governance and what steps to enchance the local legislative functional control were assure good governance. It was a normative research, also called legal normative research, of  its own kind (sui generis). It normatively adopted scientific research procedures to search for truths based on scientific legal logics. In order to answer the research questions, it adopted law and regulation approach and conceptual approach. With reference to the results of the research, it was concluded: 1) A functional control is an important part in the process of good governance. In absence of the functional control, the power would be exercised subjectively and based on the individual interpretation of the power maker. A stricter functional control by the local legislatives would certainly bring positive impacts to the quality of good governance in local governments in terms of planning, execution and accountability. Accordingly, a functional control would significantly ecounrage good governance. 2) An effectively stricter legislative functional control would be realized through restrictions on regulation related with local legislative function. The local legislative functional control would be enchanced through better quality of human resources in the local legislatives. The performance of enhanced quality would be measurable based on the extend of roles of the local legislative in controlling regents/mayor;